2011
DOI: 10.1007/s10862-011-9242-9
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Wisconsin Schizotypy Scales in an Undergraduate Sample: Classical Test Theory, Item Response Theory, and Differential Item Functioning

Abstract: The Wisconsin Schizotypy Scales are widely used for assessing schizotypy in nonclinical and clinical samples. However, they were developed using classical test theory (CTT) and have not had their psychometric properties examined with more sophisticated measurement models. The present study employed item response theory (IRT) as well as traditional CTT to examine psychometric properties of four of the schizotypy scales on the item and scale level, using a large sample of undergraduate students (n = 6,137). In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
36
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 24 publications
(36 reference statements)
6
36
1
2
Order By: Relevance
“…The fit of this model was only adequate (CFI = .93, RMSEA = .057, 90% confidence interval = .044–.070). Finally, we fit the model using the 15-item short form that Winterstein et al (2011). The fit of this model was similar to that of the model with the full set of items (CFI = .93, RMSEA = .044, 90% confidence interval = .043–.055).…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…The fit of this model was only adequate (CFI = .93, RMSEA = .057, 90% confidence interval = .044–.070). Finally, we fit the model using the 15-item short form that Winterstein et al (2011). The fit of this model was similar to that of the model with the full set of items (CFI = .93, RMSEA = .044, 90% confidence interval = .043–.055).…”
Section: Resultsmentioning
confidence: 83%
“…Validity of the SAS has been sustained across a number of investigations (Chapman, Chapman, & Kwapil, 1995; Fonseca-Pedrero et al, 2008). Internal consistency from this administration was strong for the full instrument (α = .87) and the 15-item short form (α = .78) developed by Winterstein et al (2011).…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…Although the sample demographics are consistent with the demographics of the state from which it was drawn (US Census, 2010), it is unclear whether the results of the current research can be generalized to minority populations. Some previous research suggests that White participants have lower means than minority participants on these scales (Chmielewski, Fernandes, Yee, & Miller, 1995) and some items display differential item functioning between African-American and White participants and between men and women (Winterstein et al, 2011). Winterstein et al (2011) concluded that these scales need to be revised and that subsample norms should be used.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has reported cronbach’s internal reliability fluctuating between .78 and .92 for these measures, and test-retest reliability between .75 and .82 (Fonseca-Pedrero et al, 2008; Graves & Weinstein, 2004; Kwapil et al, 2008). However, one criticism of the PerAb and MagicId is that some studies have reported test-retest reliability of .63–.76 for PerAb and .73–.79 for MagicId (Winterstein, Ackerman, Silvia, & Kwapil, 2011). Factor analytic studies have found that they load on a cognitive-perceptual factor along with other measures of positive schizotypy (Cicero & Kerns, 2010; Wuthrich & Bates, 2006).…”
Section: Methodsmentioning
confidence: 99%